Inhibitory Effects of Soyeum Pharmacopuncture (SPP) on Rheumatoid Arthritis in Collagen II-induced Arthritis (CIA) Mice - Hwa-Seung Yoo; Dae-Hwan Youn; Seung-Hyung Kim; Jong-Soon Lim (Korean Pharmacopuncture Institute, 2007)
Objective : The aim is to examine the effect of Soyeum Pharmacopuncture (SPP) on collagen-induced arthritis (CIA) in DBA/1OlaHsd mice. Methods : To determine the effect of SPP on chronic IFNlammatory joint disease, we induced CIA in DBA/1OlaHsd mice by immunization with bovine type II collagen. Animals were treated with intraperitoneal injection doses of 2 mg/kg of SPP, beginning 3 days before the expected onset of disease symptoms. Inhibitory Effects of SPP were observed by serum levels of TNF-, and IFN-,,, or cell proliferation in the spleen cell culture and histological examination of knee joint. Results : In the CIA Mice, serum levels of TNF-, and IFN-,, production in the spleen cell culture were reduced. At the histopathological examination of knee joint, chondropathy of cartilage in the synovial joint in the SP group was repaired while compared with control group. Conclusion : These results suggest that the SPP may be effective for the prevention and treatment of rheumatoid arthritis disease.